Changes in treatment intent and target definition for preoperative radiotherapy after 18F-Fluorodeoxyglucose positron emission tomography in rectal cancer: A Meta-analysis. Issue 145 (December 2021) - Lee, Soo Jin; Ha, Seunggyun; Pahk, Kisoo; Choi, Yun Young; Choi, Joon Young; Kim, Sungeun; Kwon, Hyun Woo
Highlights: FDG PET changed preoperative radiotherapy plan in 24.6% of patients with rectal cancer. FDG PET helps avoid geographical misses and increase interobserver agreement. Planning target volume was not significantly different between FDG PET and conventional imaging. Abstract: Purpose: To evaluate the impact of 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) on changes in treatment plan and target definition for preoperative radiotherapy in patients with rectal cancer. Methods: Embase, PubMed, and Cochrane Library were searched up to November 2020 for all studies investigating the role of preoperative FDG PET in patients who underwent neoadjuvant radiotherapy before curative-intent surgery. The proportion of patients whose treatment plan (curative vs. palliative intent) or target definition was changed after FDG PET was analyzed. A random-effects model was used for pooled analysis. The change in target definition was compared between conventional radiological imaging-based target volume [gross tumor volume (GTV) or planning target volume (PTV)] and PET-based target volume (GTV or PTV) using the standardized mean difference (SMD) and 95% confidence interval (CI). Results: A total of 336 patients from twelve studies were included. In eight studies, PET changed either the treatment intent or target definition in 24.8% of patients (95% CI 15.1% to 37.9%, I 2  = 69%). In ten studies, the PET-based GTV was lower than the conventional imaging-based target volume (SMD −7.0, 95% CI −1.39 to −0.01). However, there was no significant difference between conventional imaging-based and PET-based PTV (SMD −0.07, 95% CI −0.75 to 0.62). In six studies evaluating the initial staging based on PET, the initial staging (nodal or metastasis status) was changed in 53 of 229 patients (23.1%). Newly detected or additional distant metastases were identified in 22 patients (9.6%) after FDG PET. Conclusion: The use of FDG PET influences radiotherapy planning in a fourth of patients with rectal cancer. FDG PET can provide additive information for accurate tumor delineation, although PET-based PTV did not significantly change. These findings suggest that FDG PET may be beneficial to patients with rectal cancer before establishing a radiotherapy plan.